The economic situation of Hungarian crop production enterprises, especially in Hajdú-Bihar county - Erdős, Adél Dorottya; Szőllősi, László (Applied Studies in Agribusiness and Commerce, 2021)
Increasing the competitiveness of Hungarian crop production plays a key role in moving forward at the international level. However, improving efficiency and profitability is essential in this regard. The natural resources in Hungary provide an excellent opportunity for crop production. About 8% of the arable land in Hungary (a total of 4.3 million hectares) belongs to farmers in Hajdú-Bihar County. This research is based on secondary data that can be found in the HCSO and EMIS databases. HCSO data was used for the comparison of national and county data characterising crop production, while the EMIS database was used to process the financial data of enterprises dealing with field crop production. The Hungarian sample size is 853, of which 69 enterprises are from Hajdú-Bihar County. The aim of this study is to assess the profitability, assets and financial situation of arable crop production enterprises operating in Hajdú-Bihar County as a function of national average data. Based on the examined profitability indicators (operating ROS and ROA), it was established that the enterprises in Hajdú-Bihar County are profitable, even in a national context. In terms of operating ROS, the farms in the examined county were able to achieve a 3.6 percentage point higher value due to their more efficient cost management, despite having a similar level of technology compared to businesses spanning across the entire country. The proportion of farms with the lowest leverage ratio (<20%) is 16 percentage points higher at the county level than at the national level. In addition, almost 70% of the enterprises operating in Hajdú-Bihar County have excellent liquidity. This rate is 50% at the national level.